Neonatal pneumothorax in congenital diaphragmatic hernia: Be wary of high ventilatory pressures. Issue 3 (18th May 2022) - Rubalcava, Nathan; Norwitz, Gabriella A; Kim, Aimee G; Weiner, Gary; Matusko, Niki; Arnold, Meghan A; Mychaliska, George B; Perrone, Erin E
Abstract : Background: Patients with congenital diaphragmatic hernia (CDH) require invasive respiratory support and higher ventilator pressures may be associated with barotrauma. We sought to evaluate the risk factors associated with pneumothorax in CDH neonates prior to repair. Methods: We retrospectively reviewed newborns born with CDH between 2014 and 2019 who developed a pneumothorax, and we matched these cases to patients with CDH without pneumothorax. Results: Twenty-six patients were included (n=13 per group). The pneumothorax group required extracorporeal life support (ECLS) more frequently (85% vs 54%, p=0.04), particularly among type A/B defects (31% vs 7%, p=0.01). The pneumothorax group had higher positive end-expiratory pressure (PEEP) within 1 hour of birth (p=0.02), at pneumothorax diagnosis (p=0.003), and at ECLS (p=0.02). The pneumothorax group had a higher mean airway pressure (Paw) at birth (p=0.01), within 1 hour of birth (p=0.01), and at pneumothorax diagnosis (p=0.04). Using multiple logistic regression with cluster robust SEs, higher Paw (OR 2.2, 95% CI 1.08 to 3.72, p=0.03) and PEEP (OR 1.8, 95% CI 1.15 to 3.14, p=0.007) were associated with an increased risk of developing pneumothorax. There was no difference in survival (p=0.09). Conclusions: Development of a pneumothorax in CDH neonates is independently associated with higher Paw and higher PEEP. A pneumothorax increases the likelihood of treated with ECLS, even with smaller defect.